Scholarship, money, and prose : behind the scenes at an academic journal - Chibnik, Michael, 1946- (University of Pennsylvania Press, 2020)
"This book is an ethnographic study of the work of editing an academic journal. The book describes the inner workings of an academic journal and what academic journals mean to the wider academic enterprise; it ponders the future of academic journals"-- Provided by publisher.